2020
DOI: 10.1111/oik.07874
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ and aboveground traits explain local abundance, and regional, continental and global occurrence frequencies of grassland plants

Abstract: Plants vary widely in how common or rare they are, but whether commonness of species is associated with functional traits is still debated. This might partly be because commonness can be measured at different spatial scales, and because most studies focus solely on aboveground functional traits. We measured five root traits and seed mass on 241 central European grassland species, and extracted their specific leaf area, height, mycorrhizal status and bud-bank size from databases. Then we tested if trait values … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…SLA is a productivity‐ and competitive ability‐related trait, that reflects species strategies for rapid acquisition of resources, with higher SLA values allowing a species to capture more light for a given biomass investment in leaves, for example (Díaz et al, 2004; Wright et al, 2004; Mariotte, 2014). In line with our findings, several studies state common species to be associated with higher SLA (Grime et al, 1997; Díaz et al, 2004; Mariotte, 2014; Lachaise et al, 2020). While species’ local abundances were best predicted by the interaction between leaf area and SLA, reflecting the leaf economics spectrum trait syndrome (Díaz et al, 2004), broad‐scale distribution metrics were best predicted by different combinations of traits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…SLA is a productivity‐ and competitive ability‐related trait, that reflects species strategies for rapid acquisition of resources, with higher SLA values allowing a species to capture more light for a given biomass investment in leaves, for example (Díaz et al, 2004; Wright et al, 2004; Mariotte, 2014). In line with our findings, several studies state common species to be associated with higher SLA (Grime et al, 1997; Díaz et al, 2004; Mariotte, 2014; Lachaise et al, 2020). While species’ local abundances were best predicted by the interaction between leaf area and SLA, reflecting the leaf economics spectrum trait syndrome (Díaz et al, 2004), broad‐scale distribution metrics were best predicted by different combinations of traits.…”
Section: Discussionsupporting
confidence: 92%
“… 1 Mariotte (2014); 2 Lavergne et al (2004); 3 Lachaise et al (2020); 4 Bruelheide et al (2018); 5 Hedge & Ellstrand (1999); 6 Grime et al (1997); 7 Eriksson & Jakobsson (1998); 8 Kolb et al (2006); 9 Van der Veken et al (2007); 10 Thompson et al (1999); 11 Guo et al (2000); 12 Oakwood et al (1993); 13 Kelly & Woodward (1996); 14 Leishman & Murray (2001); 15 Güsewell (2004). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, empirical studies found evidence that many invasive plants exert stronger competitive effects or are more tolerant to competition than many native ones (Kuebbing and Nuñez 2016;Golivets and Wallin 2018;Zhang and van Kleunen 2019). The high competitiveness of invasive aliens could be due to them having traits, such as high specific leaf area and low root tissue density (Pyšek and Richardson 2007;van Kleunen et al 2010;Lachaise et al 2021), which allow them to rapidly take up available resources, and consequently have high intrinsic growth rates (Dawson et al 2011;Zhang and van Kleunen 2019). However, as already pointed out by Baker (1974), the high competitiveness could also be due to the production of allelochemicals that suppress germination and growth of neighboring plants.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, empirical studies found evidence that many invasive plants exert stronger competitive effects or are more tolerant to competition than many native ones (Kuebbing and Nuñez, 2016;Golivets and Wallin, 2018;Zhang and van Kleunen, 2019). The high competitiveness of invasive aliens could be due to them having traits, such as high speci c leaf area and low root tissue density (Pyšek and Richardson 2007;van Kleunen et al 2010;Lachaise et al 2020), which allow them to rapidly take up available resources, and consequently have high intrinsic growth rates (Dawson et al 2011;Zhang and van Kleunen 2019). However, as already pointed out by Baker (1974), the competitiveness could also be due to the production of allelochemicals that suppress germination and growth of neighboring plants.…”
Section: Introductionmentioning
confidence: 99%